2023
DOI: 10.1097/ftd.0000000000001040
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Model and Dosing Simulation of Meropenem Using Measured Creatinine Clearance for Patients with Sepsis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Sjövall et al employed a Monte Carlo simulation to examine MEPM dosing in septic shock patients with potential augmented renal clearance [ 32 ]. They found that achieving a sufficient 100% f T >MIC against P. aeruginosa requires either a prolonged infusion of 1 g every 8 h with a 3 h infusion time or a continuous infusion of 3 g/day over 24 h. Fukumoto et al noted that in sepsis patients, with an MIC of MEPM set at 4 μg/mL, 1 g per dose (infusion time: 3–8 h), three times a day is necessary to achieve a 50% f T >MIC in patients with CLcr >85 mL/min [ 33 ]. Roberts et al used Monte Carlo simulation based on the PK parameters of MEPM in septic patients without renal dysfunction to compare the achievement rates of 50% f T >MIC among continuous, prolonged, and intermittent bolus infusions [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sjövall et al employed a Monte Carlo simulation to examine MEPM dosing in septic shock patients with potential augmented renal clearance [ 32 ]. They found that achieving a sufficient 100% f T >MIC against P. aeruginosa requires either a prolonged infusion of 1 g every 8 h with a 3 h infusion time or a continuous infusion of 3 g/day over 24 h. Fukumoto et al noted that in sepsis patients, with an MIC of MEPM set at 4 μg/mL, 1 g per dose (infusion time: 3–8 h), three times a day is necessary to achieve a 50% f T >MIC in patients with CLcr >85 mL/min [ 33 ]. Roberts et al used Monte Carlo simulation based on the PK parameters of MEPM in septic patients without renal dysfunction to compare the achievement rates of 50% f T >MIC among continuous, prolonged, and intermittent bolus infusions [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although only a few studies have investigated the population pharmacokinetics of carbapenems in septic patients, an increase in the volume of distribution is common. Fukumoto et al revealed the volume of distribution of meropenem V (V 1 +V 2 ) in patients with sepsis was 39.7L (Fukumoto et al, 2023), while Murínová et al reported an average V of 55L in patients with serious infection (Murínová et al, 2022), respectively. Both studies reported higher V of meropenem in patients with sepsis comparing with other patients, which may be caused by the increase in V of hydrophilic drugs, which is quite common in critically ill patients (Roberts and Lipman, 2006).…”
Section: Discussionmentioning
confidence: 99%